A note on the coefficient estimates for some classes of p -valent functions - Sharma, N. L. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain estimates of the Taylor – Maclaurin coefficients of some classes of p-valent functions. This problem was initially studied by Aouf in the paper “Coefficient estimates for some classes of p-valent functions” (Internat. J. Math. and Math. Sci. – 1988. – 11. – P. 47 – 54). The proof given by Aouf was found to be partially erroneous. We propose the correct proof of this result.